Exploring The Potential Technology In Personalized Learning Environment (PLE) - Che Ku Mohd, Che Ku Nuraini; Shahbodin, Faaizah; Che Pee @ Che Hanapi, Ahmad Naim (AENSI Journals, 2014)
Background: This paper explores how technology in Personalized Learning Environment (PLE) has the significant potential to become the defining technology of the twenty-first century. PLE has recently come to the discussions as a potential instructional strategy to increase student success in the online environment, yet little research exists to confirm the effectiveness of personalized learning in an online environment. Objective: A study was conducted to examine personalized learning in the online environment to determine its effectiveness on online learning. Results: The paper also highlights technical environment in creating a PLE, how does PLE works and also the implications for teaching and learning. Conclusion: In conclusion, there is a need to focus the challenge of educators towards PLE adoption and integration of technology. Further research must be conducted for using technology to successfully accomplish personalization.